Letter of sympathy to Gertrude and Elizabeth Bannister from a nun at the Convent of the Holy Faith, Glasnevin, Dublin, on the death of Roger Casement - Bannister, Gertrude, d. 1950; Bannister, Elizabeth (1916)
"Words fail to express the depth of my feeling for you in this most bitter sorrow. I had hoped to the last that the united prayers of so many would be granted ... What a glorious death - he was perfectly resigned to Almighty God's appointment - he bore no ill-will to his murderers - he loved God, he loved his fellow men and he died for his country..."
Keywords: Bannister, Gertrude, -- d. 1950 -- Correspondence; Bannister, Elizabeth -- Correspondence; Casement, Roger, -- 1864-1916 -- Death and burial